El tiempo fundamental. Tres aproximaciones: Mangabeira, Husserl y Scheler - Carbajal, César (2024)
We start from Roberto Mangabeira’s pragmatic and natural philosophical proposal of a real time, which concludes in a skepticism regarding knowledge of the world. We deepen the matter phenomenologically, focusing on some of Husserl’s developments in his 1917-1918 Bernau Manuscripts and conclude that his notion of absolute time is a correlate of absolute consciousness. We continue with Scheler’s phenomenological proposal, focusing on his 1927 paper Idealism-Realism, we then find that time has a fictitious character but based on an absolute time, although not devoid of perspectivism.